An Easy And Fast Method For Production Of Chinese Hamster Ovary Cell Line Expressing And Secreting Human Recombinant Activin A - Hassan Rassouli; Ali Sayadmanesh; Siamak Rezaeiani; Zahra Ghezelayagh; Mohammad Reza Gharaati; Tahamtani Yaser (Cell Journal, 2020)
Objective Growth factors are key elements of embryonic stem cell (ESC) research. Cell line development in eukaryotes is a time-consuming procedure which usually takes 12-18 months. Here, we report an easy and fast method with which production of Chinese hamster ovary (CHO) cells that express and secrete recombinant Activin A, as a major growth factor in endo/mesoderm differentiation of embryonic stem cells is achieved within 3-4 weeks.